Tracking key CAADP indicators and implementation processes [In the 2023 ATOR] - Collins, Julia; Tefera, Wondwosen; Yamdjeu, Augustin Wambo (AKADEMIYA2063, 2023)
2023 marks two decades since the 2003 launch of the Comprehensive Africa Agriculture Development Programme (CAADP), a continentwide framework for agriculture-led development. The implementation of CAADP has coincided with a period of strong agricultural and economic growth across Africa. CAADP has been credited with galvanizing increased recognition by the international community of the key role agriculture plays in broader economic development on the continent (Benin et al. 2018). After the first decade of implementation, the CAADP agenda was deepened through the 2014 Malabo Declaration on Accelerated Agricultural Growth and Transformation for Shared Prosperity and Improved Livelihoods (AUC 2014). Through the Malabo Declaration, African leaders recommitted to the principles and values of CAADP, including evidence-based planning, dialogue, and review, and reaffirmed the original CAADP targets of achieving 6 percent annual agricultural growth and 10 percent of public expenditures being directed to agriculture. The 2014 Declaration further expanded the CAADP commitments to include sharply reducing hunger and poverty, expanding intra-continental trade, building resilience to the adverse effects of climate change, and strengthening mutual accountability for CAADP-focused actions and results to advance agricultural transformation in Africa. The CAADP Biennial Review was designated as the operational tool to monitor the progress of African countries toward achieving these commitments.